Efficacy and safety of eslicarbazepine acetate versus controlled‐release carbamazepine monotherapy in newly diagnosed epilepsy: A phase III double‐blind, randomized, parallel‐group, multicenter study. (25th January 2018) - Trinka, Eugen; Ben‐Menachem, Elinor; Kowacs, Pedro A.; Elger, Christian; Keller, Birgit; Löffler, Kurt; Rocha, José Francisco; Soares‐da‐Silva, Patrício
Summary: Objective: We assessed the efficacy and safety of once‐daily eslicarbazepine acetate in comparison with twice‐daily (BID) controlled‐release carbamazepine (carbamazepine‐CR) monotherapy in newly diagnosed focal epilepsy patients. Methods: This randomized, double‐blind, noninferiority trial (NCT01162460) utilized a stepwise design with 3 dose levels. Patients who remained seizure‐free for the 26‐week evaluation period (level A: eslicarbazepine acetate 800 mg/carbamazepine‐CR 200 mg BID) entered a 6‐month maintenance period. If a seizure occurred during the evaluation period, patients were titrated to the next target level (level B: eslicarbazepine acetate 1200 mg/carbamazepine‐CR 400 mg BID, level C: eslicarbazepine acetate 1600 mg/carbamazepine‐CR 600 mg BID) and the evaluation period began again. The primary endpoint was the proportion of seizure‐free patients for 6 months after stabilization in the per protocol set. The predefined noninferiority criteria were −12% absolute and −20% relative difference between treatment groups. Results: Eight hundred fifteen patients were randomly assigned; 785 (388 in the eslicarbazepine acetate group and 397 in the carbamazepine‐CR group) were included in the per protocol set, and 813 (401 in the eslicarbazepine acetate group and 412 in the carbamazepine‐CR group) were included in the full analysis set for the primary analysis. Overall, 71.1% of eslicarbazepine acetate–treated patients and 75.6% of carbamazepine‐CR–treated patients were seizure‐free for ≥6 months at the last evaluated dose (average risk difference = −4.28%, 95% confidence interval [CI] = −10.30 to 1.74; relative risk difference = −5.87%, 95% CI = −13.50 to 2.44) in the per protocol set. Rates of treatment‐emergent adverse events were similar between groups for patients in the safety set. Noninferiority was also demonstrated in the full analysis set, as 70.8% of patients with eslicarbazepine acetate and 74.0% with carbamazepine‐CR were seizure‐free at the last evaluated dose (average risk difference = −3.07, 95% CI = −9.04 to 2.89). Significance: Treatment with eslicarbazepine acetate was noninferior to BID carbamazepine‐CR. With its once‐daily formulation, eslicarbazepine acetate provides a useful option for first‐line monotherapy for adults with newly diagnosed epilepsy and focal onset seizures.